دراسة تسويق محصول الشوندر السكري في منطقة الغاب. - محمد, لينا عبد اللطيف; يعقوب, غسان (Latakia University Journal -Biological Sciences Series, 2014)
تضمنت الدراسة واقع تسويق محصول الشوندر السكري في سورية بشكل عام، وفي منطقة الغاب بشكل خاص، وقد أظهرت نتائج البحث أنّ المشاكل والصعوبات التي يعاني منها تسويق الشوندر السكري تعود إلى عدم تقيّد المزارعين بموعد الزراعة المناسب وبالمساحة المخصصة لزراعة محصول الشوندر السكري والمقررة من قبل الهيئة العامة لإدارة وتطوير الغاب، بالإضافة إلى عدم قيام الوحدات الإرشادية بدورها في توفير بطاقات التوريد بالموعد المناسب وبالكميات الكافية للمزارعين نتيجة تحكم نظام المحسوبيات بعملية توزيع بطاقات التوريد في الوحدات الإرشادية، بالإضافة إلى انخفاض الطاقة التصنيعية لمعمل السكر، وعدم قدرته على استيعاب الكميات المنتجة والزائدة عن الخطة الزراعية، إلى جانب أعطال المعمل المتكررة نتيجة قدم الآليات المستخدمة فيه، وحاجتها المتكررة للصيانة، وانخفاض كفاءة بعض أقسام المعمل، وتحكم نظام المحسوبيات بتحديد درجة الحلاوة، كما أظهرت نتائج البحث أيضاً ارتفاع التكاليف الإنتاجية والتسويقية لمحصول الشوندر السكري وبشكل أعلى من سعره . The study included the reality of marketing crop sugar beet in Syria in general, and in al ghabb 's area , in particular, has shown results that the problems and difficulties of marketing sugar beet back to the non-compliance of farmers date of Agriculture appropriate and space devoted to the cultivation of the crop sugar beet and assessed by the General Authority to manage and develop Al Ghabb's area, in addition to the failure of the extension units in turn supply the deadline cards provide timely and sufficient quantities to farmers as a result of the process control system of favoritism in the distribution of cards supply extension units. In addition to the low energy manufacturing to the sugar mill, and its inability to absorb the quantities produced in excess of the agricultural plan, along with breakdowns lab frequent result gave the mechanisms used in it, and the need for frequent maintenance, and low efficiency of some sections of the lab, and the control system favoritism determine the degree of sweetness, as shown by the results Search also "high production and marketing costs for sugar beet crop and is higher than its price.